Qur’ān Interpretations of Hamzah Fansuri (CA. 1600) and Hamka (1908-1982): A Comparison - Steenbrink, Karel (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1995)
The process of Islamization of the archipelago in a broad scale only after the 12th century. At that time, the Islamization of society not only touch the fringe. Some kingdoms in the archipelago, especially those located on the island of Sumatra, began to embrace Islam. Furthermore, the conversion process is running more intensive and reach the various kingdoms in other areas.One of the important themes in seeing the Islamic tradition in this region is the struggle of Muslim thinkers in interpreting Islamic doctrines. Melee views in this area encourages thinking patterns as well as other actions in the context of religious life as a whole. One of the prominent thinkers in this field is Fansuri Hamzah.DOI: 10.15408/sdi.v2i2.835